SYIRKAH DALAM PEMAHAMAN EKONOMI ISLAM SEBUAH SOLUSI PERMASALAHAN PERMODALAN - Zakiyatun Nufus (Institut Agama Islam Agus Salim Metro Lampung, 2020)
According to the term referred to as syirkah, the fuqaha have different opinions. Abdurrahman al-Jaziri in Suhendi summarizes these opinions, among other things, according to Sayyid Sabiq syirkah is a contract between two people associated with the main assets (capital) and profit. According to Muhammad al-Syarbini al-Khatib, what is meant by Syirkah is the determination of rights to something for two or more people in a well-known or known way. According toSyihab al-Din al-Qalyubi wa Umaira what is meant by syirkah is the determination of rights to something for two or more people. Imam Taqiyuddin Abi Bakr Ibn Muhammad al-Husaini also said that syirkah is like the determination of a right on something one for two or more people in a known way. The opinion of Imam Hasbie Ash-Shidieqie that what is meant by syirkah is a contract that applies between two or more people for ta'awun in working on a business andsharing the profits. Meanwhile, Idris Muhammad said that a syirkah is the same as a trading company, that is, two or more people both promise to work together in trade by handing over their respective capital where the profits and losses are calculated according to the size of each capital.